Hubungan lama penggunaan gadget dengan perilaku sosial anak prasekolah - Emri Oktaresa Putri; Agnita Utami; Raja Fitrina Lestari (Jurnal Cakrawala Promkes, 2020)
Gadgets are used by all people including preschool children. The use of gadgets in pre-school increase every year and can make the child social behaviour is impaired because addicted to gadget duration play more than 1 hour. This study aims to see the long relationship between the use of gadgets and the social behaviour of pre-school children. This type of research is quantitative using a description of correlation design with a cross-sectional approach. The sampling technique used was consecutive sampling with a sample of 76 respondents. The data collection tool used is a questionnaire. The results of this study indicate that as many as 46.1% of children use gadgets more than 1 hour every day and 27.6% of children have bad socialization behaviour. Chi-square correlation test results obtained  = 0.003 (p <0.05), which means that there is a significant relationship between the duration of the use of gadgets and the social behaviour of pre-school children in TK Negeri Pembina 3 Pekanbaru. The results of this study are expected to provide knowledge to parents who have pre-school children to limit children in using gadgets.